Chaotic Statistical Downscaling (CSD): Application and Comparison in the Bogotá River Basin - Duarte, Freddy Santiago; Santos Granados, Germán Ricardo (Ed. Easy Chair Publications, 2018)
This study presents a new statistical downscaling method called Chaotic Statistical Downscaling (CSD). The method is based on three main steps: Phase space reconstruction for different time steps, identification of deterministic chaos and a general synchronization predictive model. The Bogotá river basin was used to test the methodology. Two sources of climatic information are downscaled: the first corresponds to 47 rainfall gauges stations (1970-2016, daily) and the second is derived from the information of the global climate model MPI-ESM-MR with a resolution of 1,875° x 1,875° daily resolution. These time series were used to reconstruct the phase space using the Method of Time-Delay. The Time-Delay method allows us to find the appropriate values of the time delay and the embedding dimension to capture the dynamics of the attractor. This information was used to calculate the exponents of Lyapunov, which shows the existence of deterministic chaos. Subsequently, a predictive model is created based on the general synchronization of two dynamical systems. Finally, the results obtained are compared with other statistical downscaling models for the Bogota River basin using different measures of error which show that the proposed method is able to reproduce reliable rainfall values (RMSE=73.37).

Este estudio presenta un nuevo método estadístico de reducción de escala denominado Chaotic Statistical Downscaling (CSD). El método se basa en tres pasos principales: Reconstrucción del espacio de fase para diferentes pasos temporales, identificación del caos determinista y un modelo predictivo de sincronización general. Para probar la metodología se utilizó la cuenca del río Bogotá. metodología. Se escalan dos fuentes de información climática: la primera corresponde a 47 estaciones pluviométricas (1970-2016, diaria) y la segunda se deriva de la información del modelo climático global MPI-ESM-MR con una resolución de 1,875° x 1,875° de resolución diaria. Estas series temporales se utilizaron para reconstruir el espacio de fase mediante el método del tiempo de retardo. El método Time-Delay nos permite encontrar los valores adecuados del retardo temporal y la dimensión de incrustación para captar la dinámica del atractor. Esta información se utilizó para calcular los exponentes de Lyapunov, lo que demuestra la existencia de caos determinista. Posteriormente, se crea un modelo predictivo basado en la sincronización general de dos sistemas dinámicos. dinámicos. Finalmente, los resultados obtenidos se comparan con otros modelos estadísticos de downscaling de la cuenca del río Bogotá utilizando diferentes medidas de error que muestran que el método propuesto es capaz de reproducir valores de precipitación confiables (RMSE=73.37).
Keywords: Agricultura; Agua - Distribución; Gestión eficiente del agua; Agrícultura; Efficient water manageme; Agricultural